Prevalence and Severity of Psychiatric Disorders and Suicidal Behavior in Service Members and Veterans With and Without Traumatic Brain Injury: Systematic Review. Issue 1 (January 2020) - Greer, Nancy; Sayer, Nina A.; Spoont, Michele; Taylor, Brent C.; Ackland, Princess E.; MacDonald, Roderick; McKenzie, Lauren; Rosebush, Christina; Wilt, Timothy J.
Abstract : Objectives: Assess prevalence and severity of posttraumatic stress disorder, suicidal behavior, and depressive, substance use, and anxiety disorders in US service members or Veterans with and without a deployment-related mild traumatic brain injury (TBI) (mTBI). Design: Systematic review using multiple databases (January 2000 to October 2017). We included national or geographically diverse samples. Main Measure: Prevalence and severity of psychiatric conditions based on diagnostic codes, clinician assessments, and self-report measures with results stratified by sample type. Results: We identified 11 studies on the basis of national samples and 22 studies on the basis of geographically diverse samples. Traumatic brain injury severity was not always ascertained or reported. In national studies, posttraumatic stress disorder, depressive disorder, substance use disorder, and anxiety disorder prevalence were higher in those with TBI than in those without. One national sample reported prevalence of suicide attempts. Across psychiatric conditions, strength of evidence ranged from insufficient to moderate. In geographically diverse samples, the pattern of findings was similar. National studies provided insufficient evidence on psychiatric condition severity; geographically diverse studies found greater severity of posttraumatic stress disorder symptoms with mixed results for symptoms of depressive or substance use disorders. Conclusions: Service members and Veterans with TBI history have higher prevalence and possibly severity of selected psychiatric conditions. Abstract : Supplemental Digital Content is Available in the Text.